Distinct Responses of Gut Microbiota to Jian-Pi-Yi-Shen Decoction Are Associated With Improved Clinical Outcomes in 5/6 Nephrectomized Rats - Zheng, Lin; Chen, Shuo; Wang, Fochang; Huang, Shiying; Liu, Xinhui; Yang, Xilan; Zhou, Haokui; Zhao, Guo-Ping; Luo, Mingjing; Li, Shunmin; Chen, Jianping (Frontiers in Pharmacology, 2020)
Gut dysbiosis contributes to the development and progression of chronic kidney disease (CKD) and its complications. However, the effect of drugs on the gut microbiota of CKD patients and its influence on treatment outcomes remains to be explored. Here, we assessed whether the response of gut microbiota to the traditional Chinese medicine Jian-Pi-Yi-Shen (JPYS) decoction differed from that to piperazine ferulate (PF), a kidney-targeted drug, by 16S rDNA sequencing, and whether the difference could be linked with drug-specific clinical outcomes. We showed that both JPYS and PF improved renal function, but only JPYS was able to restore the blood reticulocyte counting and serum calcium level in CKD rats. We also found that weighted UniFrac beta-diversity of the gut microbiome of the JPYS treated rats was significantly different from that of PF. Microbiome markers of drug-specific response were identified and subjected to correlation network analysis, together with clinical parameters and KEGG pathways. Among the microbiome markers of CKD, Corynebacterium was found to form a network hub that was closely correlated with the JPYS responder Enterococcus, suggesting a potential indirect impact of JPYS on Corynebacterium via interspecies interactions. We also identified two network hubs of the PF responder Blautia and the JPYS-only marker Coprococcus, which were connected with many genera and clinical parameters. They might serve as keystone taxa driving the response of gut microbiota to the drugs and influence host outcomes. Moreover, the JPYS-only marker Clostridium_XIVb was found to be connected to many pathways that are associated with CKD progression and might account for the improved outcomes in the JPYS treated rats. At last, the identified keystone markers of drug response were validated by qPCR for their differential abundance between CKD and the two drugs. Taken together, our study revealed that the responses of gut microbiota to JPYS were distinct from that to PF, and pinpointed drug-specific keystone microbiome markers closely correlated to clinical parameters, which could serve as candidate microbiome targets for further studies on their roles in medicating the drug efficacy of TCM in CKD.